The representation of Byzantine history in high school textbooks in Turkey. (4th September 2014) - Durak, Koray
Abstract : Examining the treatment of Byzantium in the history textbooks that were used in Turkish secondary education from the foundation of the Turkish republic in 1923 to the present, I argue that the history of this treatment can be divided roughly into four periods, during which the Turkish, Graeco-Roman, and Islamic parts of Anatolian history have been differently emphasized depending on the current ideological concerns. The presentation of Byzantium has diminished progressively since the beginning of the republican period, both in volume and scope, and is currently dwarfed by the extensive and detailed treatment of Turkish and Islamic history. A negative image of Byzantium is produced and disseminated in the textbooks through mechanisms of exclusion, overemphasis, and distortion.